Innovation, Entrepreneurship and their effect on Economic growth - Al-Baddawi, Eman Awad (Journal of Economic, Administrative and Legal Sciences, 2022)
This research paper aims to investigate innovation and entrepreneurship as two concepts that have spread in the recent period and to show the relationship between them. This study is based on the descriptive approach to achieve the objectives of the study, as through a review of previous studies and articles in this regard, I tried to provide a simplified definition of the terms “innovation and entrepreneurship”, and then clarify the relationship between them and their types according to recent studies, so that the matter does not get mixed up. As is common, the impact of each of them on the economy has been determined. The review of selected previous studies showed that the concept of innovation and entrepreneurship did not take a sufficient percentage of studies and research, so related topics were added to stimulate work on them in the future. The results of the research indicated that entrepreneurship and innovation have an important impact on the economic performance of countries. This study recommends that innovation and entrepreneurship should be given greater attention by policy makers in countries, especially in Arab countries.
Keywords: innovation; entrepreneurship; economics